Memoria, ideologia e identità nazionale nelle rivisitazioni sette-ottocentesche dell’elogio della lingua portoghese - Monica Lupetti (Caietele Echinox, 2023)
Numerous Portuguese texts and paratexts from the era of the dual monarchy (1580-1640) are characterised by eulogies of the Lusitanian language that fulfill the task of defending its prestige over Spanish. Between the end of the 18th century and the first half of the 19th century, when the production of translations, grammars, dictionaries and other glottodidactic tools of various natures increased, the memory of the ancient praises was relied upon for purposes that were (justifying the study of Portuguese as a foreign language), politicocultural (defending the dignity of Portuguese within the neo-Latin stock; making space for the Lusitanian literary tradition in the European cultural space), and commercial (in the context of the modern publishing industry, creating a market for Lusophone texts and manuals).